Treating chronic oedema of the lower limb using circular knit garments: how garment characteristics affect outcomes. (1st October 2021) - Phillips, Natalie; Lawrance, Sue; Everett, Jeanne
Abstract : The use of compression therapy to treat chronic oedema of the lower limbs can be a challenge, especially when this is undertaken by clinicians who have limited experience and knowledge of the theoretical principles which underpin its use in clinical practice. This articles aims to discuss the reasoning which underpins the use of compression hosiery in the management of lymphoedema and how this understanding can improve treatment outcomes and reduce the burden of disease on patients and clinical resources.